(untitled) (The University of Nairobi Journal of Language and Linguistics, 2024)
This paper describes the morphological, morphophonological, morphosyntactic and semantic properties of the pronominal system of the Nessuit variety of Okiek – a branch in the Kalenjin language family in the Southern Nilotic subdivision (Rottland 1982, 1983) of the Nilo-Saharan phylum (Greenberg 1963). The data used in this paper consists of wordlists, phrases and sentences collected through elicitation interviews, from short stories, and from real life speech events during fieldwork conducted by the author in Nessuit town in the Nakuru County of Kenya between 2019 to 2022. The findings show that: (1) there are five sets of pronominal morphemes (personal, demonstrative, possessive, interrogative, and relative pronouns); (2) personal, demonstrative, and possessive pronouns can occur as independent or bound grammatical items; (3) interrogative pronouns occur as independent items; (4) the pronominal system is associated with the grammatical categories of number, tense, aspect, person and case; (7) all bound pronominal elements are suffixes except for bound subject pronouns which are prefixes; (8) bound pronominal elements are subjected to vowel harmony with the exception of bound possessive pronouns; (9) the distribution of bound demonstrative suffixes is governed by tense and aspect categories; (10) independent possessive pronouns are morphosyntactically linked to the head noun by a relative pronoun; and (11) certain verbal and nominal phrases are used for a function that is expressed by indefinite pronouns in English. These findings complement the study of the pronominal system of the Mariashoni variety of Okiek by Micheli (2018) and form a base for further explorations of Okiek and comparative investigations into Southern Nilotic grammar.